Effective response in nonlinear spherical coated composites under external AC and DC electric fields - 包曙红 陈小刚 李倩倩 郭军明 翟丽丽 (Chinese physics B, 2012)
By using the perturbation method, effective nonlinear direct current （DC） and alternating current （AC） responses of nonlinear composites with spherical coated inclusions randomly embedded in a host medium are studied under the action of an external electric field Ea = E0 ＋ E1 sinωt ＋ E3 sin 3ωt with different amplitudes and frequencies. The local potentials of composites at all harmonics are given in the inclusion particles and the host regions. All effective nonlinear responses to composites and the relationship between the effective nonlinear responses at all harmonics are also deduced for the spherical coated inclusions in a dilute limit.